The Influence Of Learning Discipline and Learning Motivation On Students’ Learning Outcomes In Economics Among Grade X Students At SMA Kampus Nommensen Pematangsiantar (Academic Year 2025/2026) - Susmita Bakkara; Anggun Tiur Ida Sinaga; Anton Luvi Siahaan (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines the influence of learning discipline and learning motivation on students’ learning outcomes in Economics among Grade X students at SMA Kampus Nommensen Pematangsiantar in the 2025/2026 academic year. The study employed a quantitative approach with a descriptive research design. The population consisted of all Grade X students, and a saturated sampling technique was applied, resulting in 87 students as research participants. Data were collected using questionnaires on learning discipline and learning motivation, as well as documentation of students’ Economics learning outcomes. Data analysis techniques included multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination.